MANAJEMEN KEPALA SEKOLAH DALAM MENGEMBANGKAN SARANA DAN PRASARANA SEKOLAH DI SDN KIDULDALEM I BANGIL - Rosida, Ani Yanti; Faizah, Iva; Sulistiyorini, Novi; Faizin, A. (STKIP Pesisir Selatan, 2025)
This study aims to analyze the principal’s management in developing school facilities and infrastructure at SDN Kiduldalem I Bangil, focusing on how the principal’s leadership role contributes to improving the quality of educational facilities and learning processes. The phenomenon studied reflects the challenges faced by public elementary schools in managing facilities effectively amid limited resources. The research employed a qualitative approach with a case study design, which allows for an in-depth understanding of managerial and social contexts within the school. Data were collected through in-depth interviews with the principal, direct observation of the school environment, and document analysis of administrative records such as the School Work and Budget Plan (RKAS) and infrastructure reports. The results revealed five main themes: (1) participatory planning based on school needs, (2) collaborative and transparent implementation, (3) maintenance based on collective responsibility, (4) transformational and innovative leadership, and (5) the impact of development on learning quality. The principal acted as a change agent by emphasizing collaboration, mutual cooperation (gotong royong), and community-based innovation. These findings indicate that effective school management is not merely administrative but also involves a transformational leadership dimension that fosters an adaptive and sustainable organizational culture.